Kebutuhan Sumber Belajar Dosen yang Mendukung Pembelajaran Berbasis Teknologi Informasi dan Komunikasi Di Perguruan Tinggi - Imam Fitri Rahmadi; Khaerudin; Cecep Kustandi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2018)
A lecturer must continue to develop his knowledge in a sustainable manner which is facilitated by the higher education by providing complete, relevant, and up-to-date learning resources. However, before providing learning resources, it is necessary to first analyze the needs of learning resources. This study aims to obtain information about the trends in the types of learning resources required by the Jakarta State University (UNJ) lecturers who support Information and Communication Technology (ICT) -based learning. The study was conducted using a survey method using a questionnaire filled in by 114 lecturers from 7 faculties at UNJ. Lecturers at each faculty tend to choose different types of learning sources, but video and PowerPoint (PPt) are the most needed learning resources. The development of learning resources in tertiary institutions must consider the learning resources needs of lecturers at each faculty, not only as a whole at the university level.